2013
DOI: 10.1128/aem.01556-13
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Methylation by the Methanogen Methanospirillum hungatei

Abstract: c Methylmercury (MeHg), a neurotoxic substance that accumulates in aquatic food chains and poses a risk to human health, is synthesized by anaerobic microorganisms in the environment. To date, mercury (Hg) methylation has been attributed to sulfateand iron-reducing bacteria (SRB and IRB, respectively). Here we report that a methanogen, Methanospirillum hungatei JF-1, methylated Hg in a sulfide-free medium at comparable rates, but with higher yields, than those observed for some SRB and IRB. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 44 publications
1
99
0
Order By: Relevance
“…The resistance of bacteria to inorganic Hg 2+ is associated with the presence of the Hg resistance gene (merA) [16,17], which has been considered widely distributed in the phyla of Firmicutes, Actinobacteria and Proteobacteria [16]. Meanwhile, ionic Hg in anaerobic habitats may also be potentially methylated to highly toxic methylmercury (MeHg) by Hg-methylating microbes [18,19], such as sulphate-reducing bacteria (SRB) [20,21], iron-reducing bacteria (FeRB) [22,23] and methanogens [24,25]. However, little is known regarding the responses of these Hg-methylating bacteria to long-term soil Hg contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of bacteria to inorganic Hg 2+ is associated with the presence of the Hg resistance gene (merA) [16,17], which has been considered widely distributed in the phyla of Firmicutes, Actinobacteria and Proteobacteria [16]. Meanwhile, ionic Hg in anaerobic habitats may also be potentially methylated to highly toxic methylmercury (MeHg) by Hg-methylating microbes [18,19], such as sulphate-reducing bacteria (SRB) [20,21], iron-reducing bacteria (FeRB) [22,23] and methanogens [24,25]. However, little is known regarding the responses of these Hg-methylating bacteria to long-term soil Hg contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic Deltaproteobacteria are thought to be the major contributors of MeHg found in the environment (7,8), although potentially significant contributions by methanogens and fermenting bacteria have recently been discovered (9)(10)(11). In 2013, we showed that the proteins encoded by two genes in two bacteria of the Deltaproteobacteria phylum, Desulfovibrio desulfuricans ND132 and Geobacter sulfurreducens PCA, are essential for the conversion of Hg(II) to MeHg (12).…”
mentioning
confidence: 99%
“…The highest MeHg production occurs mostly in sediments at the oxic/anoxic transition zones during the anaerobic degradation of natural organic matter (Compeau and Bartha 1985;Gray et al 2004;Bravo et al 2014). Several guilds of bacteria are known to methylate IHg, notably iron-reducing bacteria (FeRB), sulfate-reducing bacteria (SRB), and methanogens (Fleming et al 2006;Kerin et al 2006;Gilmour et al 2011Gilmour et al , 2013Hamelin et al 2011;Yu et al 2013). The specific mechanisms and metabolic pathways involved in Hg methylation remains undefined, but two genes in particular (cluster hgcA and hgcB) have been shown to be required for Hg methylation (Gilmour et al 2013;Parks et al 2013).…”
Section: Introductionmentioning
confidence: 99%